Improving Students Speaking Skills Through Local Storytelling - Pratiwi, Ajeng; Rahman Hz, Benni Ichsanda (Universitas Negeri Semarang, 2024)
This study is aimed to assess the efficacy of employing local storytelling to enhance the speaking skills of grade XII students in an English language classroom, involving 18 participants from a Pivate School in Medan. Utilizing the action research method, the study implemented two intervention cycles centered on local stories, namely